The Algorithms and Principles of Non-photorealistic Graphics Artistic Rendering and Cartoon Animation - Geng, Weidong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"The Algorithms and Principles of Non-photorealistic Graphics: Artistic Rendering and Cartoon Animation" provides a conceptual framework for and comprehensive and up-to-date coverage of research on non-photorealistic computer graphics including methodologies, algorithms and software tools dedicated to generating artistic and meaningful images and animations. This book mainly discusses how to create art from a blank canvas, how to convert the source images into pictures with the desired visual effects, how to generate artistic renditions from 3D models, how to synthesize expressive pictures from textual, graphical and pictorial data, and how to speed up the production of cartoon animation sequences with temporal coherence. It is intended for researchers and graduate students in the fields of computer graphics, digital media arts, and cartoon animation. Dr. Weidong Geng is a professor at the Department of Digital Media Technology and State Key Laboratory of Computer Aided Design and Computer Graphics, Zhejiang University, China.
Simulating Artistic Media for Digitized Creation of Artworks -- Computer-aided Design of Art Patterns -- Artistic Painting by Reference Images -- Artistic Rendering for 3D Object -- Expressive Rendering -- Computer-assisted Cartoon Animation by Traditional Production Pipeline -- Novel Approaches to Computer-assisted Cartoon Animation -- Perspectives of Non-photorealistic Computer Graphics.
Keywords: Computer science; Computer graphics; Computer Science; Computer Graphics; Electronic books